Writing a Dynamic Identity: Self-Criticism in the Work of Tchicaya U Tam'Si - Chaibou Elhadji Oumarou (Studies in 20th & 21st Century Literature, 1995)
Very few Africans have had the courage to express their outrage at the stifling African traditions with the vigor and consistency of U Tam'Si. In fact, self-criticism is a major theme in Tchicaya's work as he strives to build a dynamic identity through a dynamic writing style. A dynamic identity changes with time and it is directed toward the future as opposed to static identity, which is concerned with only the past. This essay problematizes his efforts to create that identity and explores the rationale behind his self-criticism. Not content with his identity, he looks for a dynamic model that would help him free himself from both the vestiges of colonialism and from the stifling African traditions. The only true identity is created through (self-)questioning, Tchicaya U Tam'Si answers in his work. Without sure and dynamic identity, there is no sure stance from which one can look at oneself with the smile of a free person.
Keywords: Africans; outrage; express; tradition; African tradition; U Tam' Si; self-criticism; identity; dynamic identity; theme; change; time; future; static identity; past; colonialism; dynamic model; stifling; (self-)questioning; questioning; self-questioning; free person